MICROMOBIL 2040 : jouer à réduire les déplacements intra-metropolitains et alléger l'empreinte carbone grâce aux tiers-lieux hybrides - Alexandre Cuvier; Philippe Vidal; Gaetan Clémence; Alexis Lecoq (Netcom)
The question of mobility plays an important role in the writing of the metropolitan narrative. In Rouen, in the context of POPSU 3, the issue of access to centralities is particularly relevant. Our serious game project is the continuation of a prospective exercise. It investigates the modalities of access to services by avoiding the systematic use of the central locations of the metropolis. MICROMOBIL 2040 is a serious game based on the development of micro-mobilities taking advantage of the presence of hybrid third places considered for 2040. These new socio-technical devices would offer several service functionalities allowing to reduce the carbon footprint of each trip and to shorten the travel time. The game takes place in two phases: the first in 2020 and the second in 2040.